Variación, coloración y estado sistemático del pez centroamericano Cichlasoma nicaraguense (familia Cichilidae) - López, Myrna I. (Revista de Biología Tropical, 1974)
Cichlasoma balteatum and C. spilotum are placed in the synonymy of C. nicaraguense on the basis of a review of the literature and examination of fresh material from Lake Nicaragua and the Atlantic slope of Costa Rica. Observations on coloration and caudal fin scalation are included.